La relève : un lieu de construction du collectif pour gérer la sécurité - Christelle Casse; Sandrine Caroly; Marc Tesson (Perspectives Interdisciplinaires sur le Travail et la Santé)
Serious accidents, which occurred in road tunnels in the 2000’s, have revealed specific risks related to tunnels, along with safety management issues. The lessons learned analyses are one resource used by tunnel operators, supported by the French Tunnel Research Centre (CETU), to improve safety management. The question raised in this paper is how these processes are linked to the actual collective safety management. Based on careful analysis of shift handover of tunnel control station operators, we aim to show what makes them a means for sharing feedback, managing safety and building a collective structure. We will thus highlight the strength of communication dynamics to design innovative safety management tools within a high-risk industrial environment.Serious accidents that occurred in road tunnels in the 2000’s revealed specific risks related to tunnels as well as safety management issues. The question raised in this paper is how are shift handovers linked to the collective safety management. Based on a careful analysis of the shift handovers of a tunnel’s control station operators, we aim to show how they can be used to share feedback, manage safety, and build a collective structure.